Effectiveness of Plyometric Training on Improving Handball Shooting Accuracy: A Systematic Literature Review - Rahmadi, Edi; Mashud, Mashud; Warni, Herita (Indonesian Journal of Physical Education and Sport Science, 2024)
Study purpose. This study examines the effectiveness of plyometric training on improving handball shooting accuracy. Materials and methods. In this study using a prism flow diagram and using the PICO method data collection technique. By collecting national articles through google scholar, crossrev and scopus obtained through the help of the "Publish or Perish" application. Result. Based on the literature review collected by the researcher, it can be concluded that plyometric training has a significant effect on improving shooting accuracy in various sports. It optimises muscle strength, speed and coordination through explosive movements, which are essential for improving shooting performance. Plyometric not only improves physical abilities such as strength and jump height, but also improves technical skills in shooting more accurately and effectively. Therefore, the integration of plyometric training in athletes’ training programmes is highly recommended to achieve optimal shooting results. Conclusion. 1). Plyometric training has a significant effect on improving shooting accuracy in various sports. 2). It optimises muscle strength, speed and coordination through explosive movements, which are essential for improving shooting performance. 3). Plyometric not only improves physical abilities such as strength and jump height, but also improves technical skills in shooting more accurately and effectively. Therefore, it is important to choose the right training programme for athletes to achieve optimal shooting results.